Managerial Incentives to Increase Risk Provided by Debt, Stock, and Options - Anderson, Joshua D.; Core, John E. (Management Science, 2018)
We measure a manager’s risk-taking incentives as the total sensitivity of the manager’s debt, stock, and option holdings to firm volatility. We compare this measure with the option vega and with the relative measures used by the prior literature. Vega does not capture risk-taking incentives from managers’ stock and debt holdings and does not reflect the fact that employee options are warrants. The relative measures do not incorporate the sensitivity of options to volatility. Our new measure explains risk choices better than vega and the relative measures and should be useful for future research on managers’ risk choices. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2811 . This paper was accepted by Shiva Rajgopal, accounting.